Residues in Orange Fruits of Postharvest Application of Imazalil and its Effect in Green Mold Control - Lado, Joanna; Pérez Faggiani, Elena; De Nigris, Andrea; Dol, Isabel; Knochen, Moisés (Agrociencia Uruguay, 2013)
The control of green mold (caused by the fungus Penicillium digitatum) in citrus packinghouses is mainly based on the use of the fungicide imazalil (IMZ). Continued application of this fungicide caused an increase in the frequency of resistant strains, and therefore an increase in the dosage of the fungicide used. The objective of this work was to determine the IMZ fungicide residue during refrigerated storage of varieties of orange (Citrus sinensis [L.] Osbeck) cultivars Washington Navel and Valencia and its relation with green mold control. Orange fruits var. Valencia were artificially inoculated with both IMZ sensitive and IMZ resistant P. digitatum isolates while Washington Navel fruit was inoculated only with the resistant isolate. After 18-20 Agrociencia Uruguay - Volumen 17 2:83-90 - julio/diciembre 2013 84 Agrociencia Uruguay hours, the fruit was treated with 500 or 1000 mg. g-1 IMZ, either alone or combined with sodium bicarbonate (SBC) at 3%. The application of the wax included IMZ at 3000 mg.kg-1. The variables analyzed were green mold incidence and IMZ residue on the fruit. The fruit was evaluated at 12, 19, 26 and 33 days after storage and after seven days of shelf life. For Washington Navel oranges, residual IMZ was below 2.0 mg kg-1 for all treatments, applied in solution at 20 °C or 50 ºC, alone or mixed with SBC. IMZ wax application resulted in a minimum residue level of 2.48 mg kg-1 and remained high until the end of the evaluation period. For Valencia oranges, residual IMZ was below 0.70 mg kg-1 for a 1000 mg.kg-1 dosis, and doubled when applied at 50 ºC, whereas residual IMZ in wax application was always higher than 3.0 mg kg-1. IMZ resistant isolate was not controlled in any variety, even with residual IMZ levels above 3.0 mg kg-1. Sensitive isolate was effectively controlled, instead, with an average 2.0 mg kg-1 of IMZ residue, or when the fungicide was combined with SBC